Some Characterizations of Similar curves in 4D-Galilean space - Babadag, Faik (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this work, we introduce families of similar curves in 4D-Galilean space with variable transformation. Also, we obtain some characterizations of this family and some theorems. Moreover, Using new Serret-Frenet vectors of these curves, we obtain some new relationships between with nonzero curvatures of the similar partner curves and unit tangent vector T of ξ satisfies a vector differential equation of fourth order in 4D-Galilean space.